Control of populations of two-level systems by a single resonant laser pulse - Golubev, Nikolay V.; Kuleff, Alexander I. (Physical review. A, Atomic, molecular, and optical physics, 2014)
We present a simple approach allowing one to obtain analytical expressions for laser pulses that can drive a two-level system in an arbitrarily chosen way. The proposed scheme relates every desired population-evolution path to a single resonant laser pulse. It allows one to drive the system from any initial superposition of the two states to a final state having the desired distribution of the populations. We exemplify the scheme with a concrete example, where the system is driven from a nonstationary superposition of states to one of its eigenstates. We argue that the proposed approach may have interesting applications for designing pulses that can control ultrafast charge-migration processes in molecules. Although focused on laser-driven population control, the results obtained are general and could be applied for designing other types of control fields.
Gesehen am 03.09.2020